ANALISIS PENGUKURAN DAN KUALITAS PERANGKAT LUNAK (STUDI KASUS PERANGKAT LUNAK SAGE 50CLOUD) - Soetam Rizky Wicaksono; Azha Satirah Khairunnisa; Merlin Widiya Rezkita; Vincentius Alfredo (Politeknik Bisnis Indonesia, 2021)
Sage 50Cloud is one of the accounting software that previously had the name Peachtree Accounting and was produced by Sage Group plc since 1978. Because the features and integrations offered by Sage 50Cloud are good and complete compared to its competitors and there is a community that is quite rapidly developing, the Sage 50Cloud software can deemed worthy to be used as a case study in the measurement process. Where the method that can be done subjectively and will be used in the software measurement process is FPA. The results of the measurement show that a score of 1610.7 can make this software acceptable to various users.